Kegunaan Pelaporan Keuangan Untuk Pembuatan Keputusan Internal - Tunjung Probo Nirmala; Mohammad Alfian; Yeni Priatna Sari (Universitas Muhammadiyah Yogyakarta, Indonesia, 2014)
Study aims to determine the level of usefulness of financial reporting for internal decision-making based on the internal user's perception of government financial reporting. Research methods are using primary data sources through an online questionnaire to 93 employees in the Inspector General Ministry of Commerce. Research suggests there is a relationship between educational background with degree of usefulness of financial statements, but there is no statistical evidence that supports an association between the level of professional experience and level of usefulness of financial statements. In addition, it is known that the level of usefulness of accrual-based information is high in internal decision-making framework. However, it was also found that there was no difference in usefulness between accrual-based information and cash-based information for internal decision making.